2022
DOI: 10.1113/jp282609
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neural and biomechanical impairments leading to pathological toe and heel gaits using neuromusculoskeletal modelling

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…We found no exclusive effect of the investigated muscle weakness on pathological gait in SPG4 patients, which might be explained by the still remaining isometric force of more than 40%. Bruel et al (2022 ) showed that increased velocity- and force-related sensory-motor reflexes of GAS and SOL lead to pathological toe-walking patterns, which can be seen in later stages of manifest spastic patients. Furthermore, Jansen et al (2014 ) used hyper-excitability of muscle spindle length- and velocity reflex loops to simulate hemiparetic gait in a neuro-musculoskeletal model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found no exclusive effect of the investigated muscle weakness on pathological gait in SPG4 patients, which might be explained by the still remaining isometric force of more than 40%. Bruel et al (2022 ) showed that increased velocity- and force-related sensory-motor reflexes of GAS and SOL lead to pathological toe-walking patterns, which can be seen in later stages of manifest spastic patients. Furthermore, Jansen et al (2014 ) used hyper-excitability of muscle spindle length- and velocity reflex loops to simulate hemiparetic gait in a neuro-musculoskeletal model.…”
Section: Discussionmentioning
confidence: 99%
“…We introduced this cost function, since we were interested in the subtle gait changes of prodromal and early-to-moderate SPG4 subjects, who still perform a heel strike walking pattern. To simulate more severe stages of SPG4, a different cost function may be needed, to allow a less constrained gait pattern ( Bruel et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further suggestions could be provided in investigating pathological gaits. Past studies tried reproducing neural pathologies with neuromechanical simulation by extending previous controllers, in-cluding specific connections to model the pathology in the desired degree of freedom [6]. However, the controller proposed could be more suitable for studying neuropathologies like hyperreflexia considering the effects of both excessive inputs from Ia fibers and the lack of reciprocal inhibition.…”
Section: Speedmentioning
confidence: 99%